2019
DOI: 10.1589/jpts.31.724
|View full text |Cite
|
Sign up to set email alerts
|

Development and exploration of a Japanese version of the cerebral palsy quality of life for children questionnaire for primary caregivers: a pilot study

Abstract: We aimed to translate and validate a Japanese language version of the cerebral palsy quality of life for children questionnaire for primary caregivers and assess the relationship between quality of life of Japanese parents and their children's motor skills. [Participants and Methods] Fifty children (aged 4 to 12 years) and their parents (mothers) were enrolled. The parent-proxy version of the cerebral palsy quality of life for children questionnaire translated to Japanese was administered, and a validation stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…While for the nonsurgical group (Group B), the statistical analysis showed that they had a substantially (P=0.012) increased quality of life at post-treatment (1) in comparison with pre-treatment, with an improvement of 21.40%. These results are confirmed by Mutoh et al [18] , who demonstrated that physical therapy rehabilitation for CP children improved their physical, psychological, self-independence, and self-confidence states, so the child's satisfactory score improved after physical therapy sessions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…While for the nonsurgical group (Group B), the statistical analysis showed that they had a substantially (P=0.012) increased quality of life at post-treatment (1) in comparison with pre-treatment, with an improvement of 21.40%. These results are confirmed by Mutoh et al [18] , who demonstrated that physical therapy rehabilitation for CP children improved their physical, psychological, self-independence, and self-confidence states, so the child's satisfactory score improved after physical therapy sessions.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we measured just two domains, namely, the physical domain (19 items) and the psychological domain (16 items). We used the parent-proxy version (for parents of children aged 4-12 years) [18] . The items' values in each domain were summed, and the final summation of two domains was divided by the number of items in the two domains (35 items).…”
Section: Egyptian Quality Of Life Questionnaire For Cerebral Palsy (A...mentioning
confidence: 99%
“…Caregivers completed questionnaires during their visit to our healthcare facilities on the same day their children's GMFM-E scores were assessed. The Japanese version of the CP-QOL questionnaire for primary caregivers [19] was administered to primary caregivers (parents or legal guardians). It contained 66 items that comprised nine categories (family and friends, communication, health, participation, access to services, special equipment, pain and bother, and some final questions regarding your child and your health) for the evaluation of the health-related QOL and well-being of both the children with CP and their caregivers.…”
Section: Qol Evaluation Of the Caregiversmentioning
confidence: 99%
“…We hypothesized that if more appropriate methods could be employed, including participants and evaluation instruments specifically designed for CP, further positive effects of hippotherapy on caregivers' QOL could be obtained. Therefore, we conducted a pilot study to evaluate the effectiveness of hippotherapy on the health-related QOL and well-being of Japanese-speaking parents of children with CP using the Japanesetranslated version of the CP QOL-Child questionnaire for primary caregivers [19]. We also examined the relationship of the parents' QOL domains with functional improvements in their children as identified by the dimension of gross-motor activities related to daily motor activities.…”
Section: Introductionmentioning
confidence: 99%